Indonesian Criminal Law Regulation on Coral Reef Ecosystem Damage - T. Andana Harris Pratama; Muhammad Ali; Fadil Fadil (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This article aims to see how the provisions of the criminal law that apply in Indonesia are related to the protection of coral reef ecosystems. The problem is focused on the urgency of protecting coral reef ecosystems and the current criminal law regulation in Indonesia. In order to approach this problem, theoretical references are used from their books by Philipus M. Hadjon and Tatiek Sri Djatmiati who argue that in the civil law system, the first approach is the legal approach. The data were collected through the prevailing laws and regulations in Indonesia and analyzed qualitatively. This study concludes that the government has attempted to regulate the protection of coral reef ecosystems in Indonesia through legal arrangements and criminal sanctions for perpetrators of destroying coral reef ecosystems, however, punishment of perpetrators of destroying coral reef ecosystems cannot solve the damage to existing coral reefs. So that a new alternative punishment is needed for the perpetrators of destroying coral reef ecosystems in Indonesia.